Bringing Learning to Life : the Learning Revolution, The Economy and the Individual. - Bradshaw, David C. A. C. A. (Routledge library editions. Education., 2012)
In an age of intense economic competition and continual change, the ability to learn is a key factor in survival and prosperity. This book examines the changing interaction of the world economy, Britain's prospects for prosperity, the connections between different kinds of work and the learning that support them. Focusing on specific areas where changed attitudes and ways of working are long overdue, the authors show the need for a better balance between formal provision in schools, colleges and within employment, and less tangible informal learning at home and in the workplace. These, in t.